DAMPAK RISIKO BISNIS, PERTUMBUHAN PENJUALAN, LIKUIDITAS, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP STRUKTUR MODAL: STUDI KASUS PERUSAHAAN FOOD & BEVERAGE - Suyono Suyono; Novita Yulia Putri; Harry Patuan Panjaitan; Grece Valency; Muhammad Ridwan (Institut Bisnis dan Teknologi Pelita Indonesia, 2024)
ABSTRACT This study aims to analyze the effect of Business Risk, Sales Growth, Liquidity, Profitability and Company Size on the Capital Structure of food & beverage sub-sector companies listed on the Indonesia Stock Exchange in 2017-2021. The population in this study is all food & beverage sub-sector companies listed on the Indonesia Stock Exchange for 2017-2021, totaling 72 companies. The sample in this study was taken using a purposive sampling technique and a total of 43 food & beverage sub-sector companies listed on the Indonesia Stock Exchange in 2017-2021. The data collection technique used is documentation and the type of data used is secondary data. The data analysis technique used is Multiple Regression Analysis with the help of the SmartPLS application. From this study it can be concluded that Liquidity and Company Size have a significant negative effect on the Capital Structure of food & beverage sub-sector companies listed on the Indonesia Stock Exchange in 2017-2021. Meanwhile, Business Risk, Sales Growth, and Profitability are not significant to the Capital Structure of food & beverage sub-sector companies listed on the Indonesia Stock Exchange for 2017-2021. Future researchers can develop this research, such as researching different sectors, adding other variables that have not been included in this research, or changing the research period. Keywords : Business Risk; Sales Growth; Liquidity; Profitability; Company Size; CapitaL Structure ABSTRAK Penelitian ini bertujuan untuk menganalisis pengaruh Risiko Bisnis, Pertumbuhan Penjualan, Likuiditas, Profitabilitas, dan Ukuran Perusahaan terhadap Struktur Modal perusahaan subsektor food & beverage yang terdaftar di Bursa Efek Indonesia tahun 2017-2021. Populasi dalam penelitian ini seluruh perusahaan subsektor food & beverage yang terdaftar di Bursa Efek Indonesia tahun 2017-2021 sebanyak 72 perusahaan. Sampel dalam penelitian ini diambil dengan teknik purposive sampling dan berjumlah 43 perusahaan subsektor food & beverage yang terdaftar di Bursa Efek Indonesia tahun 2017-2021. Teknik pengumpulan data yang digunakan yaitu dokumentasi dan jenis data yang digunakan adalah data sekunder. Teknik analisis data yang digunakan adalah Analisis Regresi Berganda dengan bantuan aplikasi SmartPLS. Dari penelitian ini dapat disimpulkan bahwa Likuiditas dan Ukuran Perusahaan signifikan negatif terhadap Struktur Modal perusahaan subsektor food & beverage yang terdaftar di Bursa Efek Indonesia tahun 2017-2021. Sedangkan Risiko Bisnis, Pertumbuhan Penjualan, dan Profitabilitas tidak signifikan terhadap Struktur Modal perusahaan subsektor food & beverage yang terdaftar di Bursa Efek Indonesia tahun 2017-2021. Kata Kunci : Risiko Bisnis; Pertumbuhan Penjualan; Likuiditas; Profitabilitas; Ukuran Perusahaan; Struktur Modal